Convolvulus Scammonia crude Alkaloids extract induces apoptosis through microtubules destruction in mice hepatoma H22 cell line - Tawfeeq, Amer T. (Iraqi Journal of Cancer and Medical Genetics, 2012)
This study evaluated the ability of crude alkaloids extracted from the leaves of Convolvulus Scammonia to distract the microtubule network of mice hepatocarcinoma cell line (H22), which is an invasive metastasis cell line. This assessment was carried out using the immunostaining technique. The extract was able to distract the microtubules of the cells under investigation after 60 min of exposure in a concentration as little as 20 µg/ml. when DAPI staining used, the cells apoptosis was not detected in this concentration and time. The apoptotic cell have been observed when the concentration of the alkaloid extract elevated up to 80 and 100 µg/ml during the mentioned exposure time. The cells were capable of recovering there native microtubules constriction after 12 hr of the alkaloid removal from the media. The extract concentration of 1mg/Kg/Bw efficiently inhibited H22 cell line tumor growth in vivo to 97.14% in mice after three weeks treatment compared to untreated control animals